2022
DOI: 10.3389/fbioe.2022.935525
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium (VI) by a Magnetic Nanoscale Zerovalent Iron–Assisted Chicken Manure-Derived Biochar: Adsorption Behavior and Synergetic Mechanism

Abstract: Using chicken manure as raw material to prepare activated carbon as a dispersant, a novel biochar-loaded nano-zerovalent iron composite (nZVI@CMBC) was developed and applied to remove hexavalent chromium, i.e., Cr(VI), in wastewater. The dispersion of nano-zerovalent iron (nZVI) particles on the surface of chicken manure–derived biochar (CMBC) successfully inhibited the aggregation of magnetic iron particles and effectively reduced the size of nZVI particles. The results demonstrated that under acidic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Moreover, The SEM-EDX spectra ( Fig. 6 d) revealed the presence of a prominent chromium complex peak on the biochar surface, corroborating the study of Fang et al [ 83 ] that observed Cr(VI) occupying biochar pores, thereby diminishing the surface area available for adsorption.
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…Moreover, The SEM-EDX spectra ( Fig. 6 d) revealed the presence of a prominent chromium complex peak on the biochar surface, corroborating the study of Fang et al [ 83 ] that observed Cr(VI) occupying biochar pores, thereby diminishing the surface area available for adsorption.
Fig.
…”
Section: Resultssupporting
confidence: 87%
“…Biochar is a porous, C-rich, and highly aromatic solid material formed by high temperature pyrolysis under oxygenated conditions (Islam et al 2021). It has a porous structure, large speci c surface area, and many oxygen (O)-containing surface functional groups, and it can exist in a stable manner in aquatic environments (Castiglioni et al 2021;Law et al 2022;Fang et al 2022; Lonappan et al 2018). Biochars derived from agricultural wastes have been shown to be effective at removing heavy metals (e.g., Pb, Cd, and Cu) and organic pollutants from wastewater through adsorption (Hong et al 2019; Kalinke et al 2016).…”
Section: Introductionmentioning
confidence: 99%